Biomarkers for Oral Cancer: Is It a Pointless Game? - Muy-Teck Teh (Dentistry, 2024)
There are forever new biomarkers discovered every now and then, claiming for their clinical diagnostic and prognostic potentials. When is it going to end or would it ever ends at all? During the preomics era, it used to be only a handful of protein markers with well-studied in-depth mechanism of actions.